Massimo Introvigne, The Plymouth Brethren. (15th December 2019) - Cusack, Carole
Abstract : Massimo Introvigne, The Plymouth Brethren. New York: Oxford UniversityPress, 2019, pp. x + 141, ISBN: 978-0-19084-242-0 (hbk).